Genetic dilution of the Ethiopian Boran cattle - Alemayehu, N.; Gebru, G.; Ayalew, W. (Ethiopian Society of Animal Production, 2003)
Ethiopia has a well-established Plant Genetic Resources Centre in recognition of the importance of conserving plant biodiversity. The same has not been done for animal biodiversity, although the country maintains large and diverse livestock resources. Recently the Ethiopian Agricultural Organization (Ethiopian Agricultural Research Organization), The Ministry of Agriculture (MoA), Alemaya University, the Institute of Biodiversity, Conservation and Research (IBCR) and other relevant institutions and organizations are making efforts to formulate the national Livestock Breeding and Conservation Policies. This paper is originally designed to address some of the issues related to the causes of Boran breed admixing and the pastoralists perception on Boran breed genetic dilution to be presented as a part of future large scale study on problems related to Boran breed conservation and Development.The issues discussed include causes of genetic dilution; drought and conflict; restocking; natural selection; traditional resource management; deliberate crossbreeding; preliminary finding on perception of pastoral communities on genetic admixtures; and what should be done in the future.